Butanol production in acetone-butanol-ethanol fermentation with in situ product recovery by adsorption. (November 2016) - Xue, Chuang; Liu, Fangfang; Xu, Mengmeng; Tang, I-Ching; Zhao, Jingbo; Bai, Fengwu; Yang, Shang-Tian
Graphical abstract: An energy efficient process was developed for butanol production in acetone-butanol-ethanol fermentation with cells immobilized in a fibrous matrix attached to the inside wall of the stirred-tank bioreactor and butanol adsorption with activated carbon to alleviate butanol toxicity. Highlights: Activated carbon (AC) with a high capacity was selected for n -butanol adsorption. Fed-batch fermentation with AC adsorption produced ∼230% more or ∼54.6 g/L butanol. Productivity increased 32% to ∼0.45 g/L·h, with a butanol yield of ∼0.22 g/g. Thermal desorption was energy-efficient, producing a solution of 167 g/L butanol. Fermentation with AC adsorption offers an efficient process for butanol production. Abstract: Activated carbon Norit ROW 0.8, zeolite CBV901, and polymeric resins Dowex Optipore L-493 and SD-2 with high specific loadings and partition coefficients were studied for n -butanol adsorption. Adsorption isotherms were found to follow Langmuir model, which can be used to estimate the amount of butanol adsorbed in acetone-butanol-ethanol (ABE) fermentation. In serum-bottle fermentation with in situ adsorption, activated carbon showed the best performance with 21.9 g/L of butanol production. When operated in a fermentor, free- and immobilized-cell fermentations with adsorption produced 31.6 g/L and 54.6 g/L butanol with productivities of 0.30 g/L·h and 0.45 g/L·h, respectively. Thermal desorption produced a condensate containing ∼167 g/L butanol, which resulted in a highly concentrated butanol solution of ∼640 g/L after spontaneous phase separation. This in situ product recovery process with activated carbon is energy efficient and can be easily integrated with ABE fermentation for n -butanol production.